2015
DOI: 10.4209/aaqr.2015.08.0505
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Submicron Particle Size Distribution and PM2.5 Composition during an Asian Dust Storm Period in Two Urban Atmospheres

Abstract: Asian dust storms (ADS), coming from deserts of China and Mongolia, have serious environmental impact on particulate matter (PM) and other pollutants in Taiwan. This study selected two urban sites, Taipei and Kaohsiung, to evaluate the influence of ADS on air quality. During the ADS periods, the hourly PM 10 mass concentrations were 800 µg m -3 in Taipei and the 400 µg m -3 in Kaohsiung, which was three to five times higher than PM episodes during the non-ADS periods. By using the principal component analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Taiwan’s climate and weather are heavily influenced by monsoon; in summer, there is the southwest monsoon, while, in winter, there is the northeast monsoon. Taipei is typically affected by Asian Dust Storms every year from December to May of the following year [ 29 , 30 ]. To minimize influences from sandstorms, this investigation of PM 2.5 pollution sources in the Taipei metropolitan area was conducted in the summer (from 8–30 August 2017), and samples were continuously collected 24 h for a total of 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…Taiwan’s climate and weather are heavily influenced by monsoon; in summer, there is the southwest monsoon, while, in winter, there is the northeast monsoon. Taipei is typically affected by Asian Dust Storms every year from December to May of the following year [ 29 , 30 ]. To minimize influences from sandstorms, this investigation of PM 2.5 pollution sources in the Taipei metropolitan area was conducted in the summer (from 8–30 August 2017), and samples were continuously collected 24 h for a total of 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, dust aerosols from the arid and semi-arid regions of China and Mongolia could be transported to the east over long distances by the westerly circulation, thus affecting the atmospheric environmental quality in Taiwan, Korea, Japan, and the North Pacific [43][44][45][46]. A recent study also revealed that the mass concentrations of PM 10 in Taipei and Kaohsiung of Taiwan during Asian dust events were 3-5 times those of non-dust days [47]. Zhao et al [48] found that trans-Pacific transport of Asian dust may even affect the ambient PM levels in North America.…”
Section: Introductionmentioning
confidence: 99%
“…Metal species with characteristic values of over 1 in Principal Component Analysis (PCA) (SPSS v.12.0) can be classified into several groups by their sources (Allen et al, 2001;Marcazzan et al, 2001;Manoli et al, 2002;AlMomani, 2003;Azid et al, 2015;Chen et al, 2015;Liang et al, 2015). In each sampling period, the metal species, based on their characteristic values, exhibited three groups in PCA (Table 3).…”
Section: Analysis Of Particulate Metal Sourcesmentioning
confidence: 99%